2012
DOI: 10.1370/afm.1384
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Chest Radiographic Findings in Adult Patients With Acute Cough

Abstract: PURPOSE Imaging may produce unexpected or incidental fi ndings with consequences for patients and ordering of future investigations. Chest radiography in patients with acute cough is among the most common reasons for imaging in primary care, but data on associated incidental fi ndings are lacking. We set out to describe the type and prevalence of incidental chest radiography fi ndings in primary care patients with acute cough. METHODSWe report on data from a cross-sectional study in 16 European primary care ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…Another multi-center study in Europe assessed the rate of incidental ndings in patients (mean age 50-years-old, 40% male) undergoing chest radiographs for acute cough. They report a rate of "clinically relevant" ndings (comparable to our Major and Moderate ndings) of 3.1% (we report 4.8%) and report a rate of nodules, densities, and shadows of 1.8% [32]. Our nodule rate (including granulomas) was 2.2% but excluding granulomas is 0.99%.…”
Section: Discussionsupporting
confidence: 80%
“…Another multi-center study in Europe assessed the rate of incidental ndings in patients (mean age 50-years-old, 40% male) undergoing chest radiographs for acute cough. They report a rate of "clinically relevant" ndings (comparable to our Major and Moderate ndings) of 3.1% (we report 4.8%) and report a rate of nodules, densities, and shadows of 1.8% [32]. Our nodule rate (including granulomas) was 2.2% but excluding granulomas is 0.99%.…”
Section: Discussionsupporting
confidence: 80%
“…Exclusion criteria were pregnancy, lactation, treatment with antibiotics in the previous month and immunodeficiency. 14 …”
Section: Design and Study Populationmentioning
confidence: 99%
“…Incidental findings are not new to medicine and parallel medical situations may offer useful insights. For example, there is an extensive literature of incidental findings in radiology (Ahmed et al., ; Alpert and Naidich, ; van Vugt et al., ). One study reviewing whole‐body CT scans found an incidental finding rate of 86% (Furtado et al., ), and review and analysis of 44 publications on incidental findings suggested that the overall frequency of incidental findings in radiological studies was 23.6% (Lumbreras et al., ).…”
Section: What Are Genomic Incidental Findings?mentioning
confidence: 99%